Clinical profile, treatment, and outcomes of patients with COVID-19 in a tertiary referral hospital in South Sumatera, Indonesia: A retrospective single-center study - Deli Marteka; Amarila Malik; Ingrid Faustine; Nadia Farhanah Syafhan (Belitung Nursing Journal, 2022)
Background: Although there are fewer COVID-19 cases in Indonesia, the pandemic is still ongoing. COVID-19 has a significant death rate in Indonesia, but lack of information on the effect of different clinical and demographic factors on COVID-19-related grimness and mortality in Indonesia. Objective: This study examined the clinical profile, treatment, and outcomes of patients with COVID-19 at Lahat Regency Hospital in South Sumatera, Indonesia, to find relevant markers that might be utilized to predict the prognosis of these patients. Methods: This was a retrospective single-center study of all medical record files of confirmed patients with COVID-19 admitted to Lahat Hospital from September 2020 to August 2021 (n = 285). Descriptive statistics, Chi-square, Mann-Whitney, Multiple Logistic Regression, and Cox's proportional hazards model were used for data analyses. Results: This study included 65 non-hospitalized and 220 hospitalized patients. Hospitalized patients were divided into dead and alive groups. The median age was lower in the non-hospitalized group without gender discrimination, and most hospitalized patients had comorbidities. Vital signs and clinical features were significantly different in hospitalized patients compared to non-hospitalized. The survival patients in the hospitalized group showed lower white blood cell (WBC), neutrophil percentages, and neutrophil-lymphocyte ratio (NLR) but higher lymphocyte and eosinophil. Non-survival patients had elevated alanine aminotransferase (ALT), blood urea nitrogen (BUN), creatinine, blood glucose, and potassium. The use of Favipiravir and Remdesivir was significant between the alive and dead groups. The mean hospital stay for all patients was 9.49 ± 4.77 days, while the median duration of hospital time was 10.73 ± 4.33 days in the survival group and 5.39 ± 3.78 days in the non-survival group. Multiple logistic regression analysis determined respiration rate, WBC, and BUN as predictors of survival. Conclusions: Age and comorbidities are significant elements impacting the seriousness of COVID-19. Abnormal signs in laboratory markers can be used as early warning and prognostic signs to prevent severity and death. Potential biomarkers at various degrees in patients with COVID-19 may also aid healthcare professionals in providing precision medicine and nursing.